Celecoxibe versus ibuprofeno no controle da sintomatologia pós-operatória em exodontias de terceiros molares : estudo clínico randomizado duplo-cego - Barreiro, Bernardo Ottoni Braga (2018)
Third molar extraction is a surgical procedure with significant morbidity in the postoperative period. The aim of the present study was to compare postoperative effects of celecoxib (200 mg/day) and ibuprofen (1,800 mg/day) on trismus, swelling, pain and quality of life of patients subjected to extraction of third molars. A randomized double-blind clinical trial was conducted. Fifteen patients were submitted to extraction of impacted third molars, right and left, at different times. Oral dexamethasone (8 mg) was given preoperatively and for postoperative analgesia, celecoxib was administered for one side tooth extraction and ibuprofen for the other. Pain, swelling, trismus and quality of life were scored with a visual analogical scale (VAS), facial linear measurements and Oral Health Impact Profile questionnaire (OHIP-14). Trismus did not significantly differ between the groups. Angle of the mandible to the nasal border distance was significantly lower in the ibuprofen group at 0.5 h and 48 h. OHIP-14 total score was significantly lower in the ibuprofen group at 48 h, where differences occurred for functional limitation, physical pain and physical disability domains. No significant differences occurred at the other OHIP-14 times and domains. Pain VAS was significantly lower in the ibuprofen group at 4, 8, 24, 48 and 72 h. Swelling VAS was significantly lower in the ibuprofen group at 2, 6, 12, 72 and 96 h. Rescue medication was more often in the celecoxib group, but without significant difference considering the number of tablets used. Frequency of infection and duration of surgical procedure did not significantly differ between the groups.